Fraud Detection in Government in the Last Ten Years - Wana, Desty; Rohman, Abdul; Raharja, Surya (Pusat P2M Politeknik Negeri Batam, 2025)
Over the past three years, Indonesian government state losses have exhibited a noticeable upward trend. The fraud triangle theory offers valuable insights into the relationship between fraud (as manifested in state losses) and three key factors: pressure, opportunity, and rationalization. These elements are reflected in instances of revenue shortfalls, potential losses, and non-compliance with regulations. Our study analyzed data from various government entities, including the central government, local governments, state-owned enterprises (SOEs), regional-owned enterprises (ROEs), public service agencies, regional public service institutions, and other government-related agencies over the past decade (2013 to 2023). Our findings reveal that pressure stemming from revenue shortfalls, opportunities associated with potential losses, and rationalization arising from non-compliance with regulations significantly contribute to fraudulent activities within the government sector. Based on our research, the fraud triangle theory, with its focus on revenue shortfalls, potential losses, and non-compliance with regulations, provides a robust framework for identifying fraudulent practices within the government sector.